BAITUL MAL WAT TAMWIL SEBAGAI APLIKASI PROGRAM FINANCIAL INCLUSION DALAM PENINGKATAN AKSES BAGI KESEJAHTERAAN MASYARAKAT KECIL DAN MENENGAH - Nur Eka Setiowati (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2014)
AbstractAcceleration of economic growth acts as a basic requirement of the most strategic for improving the quality of life of the people. Important element in supporting the acceleration of economic growth is to optimize the contribution of the financial sector by opening up access to financial services to the widest possible public and businesses such as UMKM. That is, there should be an effort to encourage the use of the financial sector in the economy as efforts to increase public welfare. Financial Inclusion is total activity which is aimed at negating all forms of barriers both price and non-price on people's access to financial services utilize. BMT is a potential for the organization to reach the bottom layer and a microfinance institution of the most affordable and most convenient means to meet the demand for loanable funds (loan).Â Keywords : Economics Growth, Financial Inclusion, UMKM, Baitul Maal Wat Tamwil ( BMT ).